Elderly Needs for Credit Productsin NarathiwatProvince, Thailand - ทองสามสี, กันยปริณ; ทองสามสี, อิสระ (Parichart Journal, 2017)
The prevailing economic situation in the three southern border provinces of Thailand has of recent, been threaten by terrorism and natural disasters which have impeded the growth of agriculture, industry and tourism in the concerned areas. Mindful of the information has declared Narathiwat province as having the third highest proportion of poor people in southern region, Thailand. This study seeks to explore the credit-product needs and the credit-service needs of the elderly in Narathiwat. Employing questionnaire as the main research instrument, the population in this study was 67,707 elderly persons, out of which 398 were selected as the sample size with a percentage rate of 69.85 respondents. Research experts verified the content to ensure high content validity, and the questionnaire reliability score was 0.894. The results revealed that the elderly have demands for commercial credit, agricultural credit and credit for housing. The average level was between 2.51-2.77. The results further showed the factors influencing the elderly to choose their credit services which are the reliability of the financial institutions, low-interest rates, excellent interpersonal skills of the bankers, the easy-to-understand of the application form, and the locations within the community vicinity of the institutions. The results are beneficial to government agencies and financial institutions in the provision of appropriate credit products to the elderly in Narathiwat province.